2017
DOI: 10.1155/2017/3610878
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phosphate from Polluted Waters Using Calcium Alginate Beads Doped with Active Carbon Derived fromA. asperaPlant as Adsorbent

Abstract: An adsorbent prepared by entrapping active carbon derived from the stems of Achyranthes aspera plant in the calcium alginate beads (CABAA) has been investigated for its adsorption nature towards the removal of phosphate by varying various physicochemical parameters. Surface morphological studies are made using FTIR, XRD, FESEM, and EDX. The sorption mechanism is analyzed using Freundlich, Langmuir, Dubinin-Radushkevich, and Temkin adsorption isotherms. The adsorption kinetics is found to follow the pseudo-seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The adsorbents derived from bio-materials are attracting the attention of the researchers in controlling various dyes. In fact, our research group made some progress in this aspect and found interesting results and they have been reported to the literature (Sujitha & Ravindhranath 2017a, 2017b, 2018bNaga Babu et al 2018).…”
Section: Introductionsupporting
confidence: 54%
“…The adsorbents derived from bio-materials are attracting the attention of the researchers in controlling various dyes. In fact, our research group made some progress in this aspect and found interesting results and they have been reported to the literature (Sujitha & Ravindhranath 2017a, 2017b, 2018bNaga Babu et al 2018).…”
Section: Introductionsupporting
confidence: 54%
“…Of these, adsorption methods are interesting as they are based on easily accessible materials, simple in operation, economical and effective. [13] Active carbons obtained from different bio-materials, [14,15] bone char, [16] natural zeolites, [17] Ca-alginate beads doped with Al 2 O 3 nano flakes and C.urens seeds active carbon, [18] exhausted coffee grounds [19] are some of many adsorbents reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…While entrapment of adsorbents using alginate beads has been extensively investigated for the uptake of various metals (Wang et al 2017), few studies have focused on the uptake of phosphate from solution. Sujitha and Ravindhranath (2017) reported an exceptionally high phosphate adsorption capacity of 133.3 mg=g by calcium alginate beads doped with active carbon derived from the Achyranthes aspera plant. However, activated carbon is expensive to produce and may not be the most viable option.…”
Section: Introductionmentioning
confidence: 99%